Mitigating flood risk in Malaysia through flood insurance: Exploring the feasibility of the United States and Japanese approaches - Mohd Rozaimy, Ridzuan; Jamal Rizal, Razali; Ju, Soon-Yew; Norhidayah, Md Yusof; Kong, Lai-Kuan; Nur Hidayahtul Nabihah, Manas; Noor Amira Syazwani, Abd Rahman (Human Resource Management Academic Research Society (HRMARS), 2023)
Floods have the potential to occur in any location and at any time due to sustained rainfall lasting for several days. In light of these situations, governments that are hesitant to assume these heightened risks may perceive a greater desirability in expanding the involvement of private insurance companies. Nevertheless, the inherent communal nature of these risks necessitates active government intervention to provide sufficient insurance coverage. While there have been considerable studies conducted on flood insurance, there is a noticeable dearth of studies that particularly examine the flood insurance structure in Malaysia. The efficacy of catastrophe recovery in developed nations is contingent upon the crucial functions fulfilled by insurance and government assistance. Nevertheless, it is less common for developing nations to engage in such practices. Hence, this study aims to analyze the flood insurance approaches employed in the United States and Japan. Additionally, the secondary objective involves assessing the current state of flood insurance practices in Malaysia and evaluating its feasibility in adopting flood insurance strategies similar to those implemented in the United States and Japan. This study adopts a library-based approach, and the expected outcome of this research is to propose recommendations for Malaysia to improve its flood insurance system. This investigation adds to the existing body of knowledge by offering fresh perspectives on the efficacy of flood insurance practices in the United States and Japan, and their applicability within the context of Malaysia